Target Costing in an Effort to Increase Profits - Taroji, Bunyamin Achmad; Ilmiyono, Agung Fajar; Octavianty , Ellyn (Jurnal Indonesia Sosial Sains, 2025)
Target Costing is a strategic approach in cost management that begins with determining the selling price of a product based on market conditions and consumer preferences, then setting the expected profit, and from there determining the maximum cost allowed to produce the product. This is very good for companies to implement so that companies can manage costs well and achieve company profits. The purpose of this study is to analyze the effectiveness of implementing target costing in an effort to increase company profits. The method used is descriptive qualitative. The results of the study show that the calculation of target costing at Mazdar Collection can increase company profits by 27%, including 39% from jacket sales and 26% from sales of almamater uniforms. So Mazdar Collection should implement the target costing method in order to achieve the expected profit.